Service Readiness of Primary Health Care Facilities for Non-Communicable Diseases Management - Sharma, Yam Prasad; Kaphle, Hari Prasad; Shrestha, Niranjan; Upadhyay, Jagat Prasad; Poudel, Sujan (Journal of Nepal Health Research Council, 2024)
Background: NCDs prevalence and associated risk factors impacts on the burden of disease and premature mortality. Effective NCD service delivery requires well equipped facilities with trained providers and resources. Evaluating readiness and its determinant is crucial for enhancing NCD management. The study examines readiness in primary health care facilities for managing non-communicable disease in Syangja district. Methods: A cross-sectional research was conducted among 117 Primary health care facility health workers in Nepal's Syangja District. The data was collected through face-to-face interviews using modified WHO-SARA tool. The chi-square test was used to evaluate the relationship between NCD readiness and its associated factors and multivariable logistic regression was utilized to determine the strength of the correlation. Results: Only 6 percent of the healthcare facilities in Syangja district had developed the system for readiness against non-communicable diseases. The mean percentage scores for service-specific domains ranged from 40% to 58%, indicating variations in readiness across different domains mainly contributed by basic amenities and training. Approximately 80.3% of health facilities received support from the local government, while equipment or commodities support was provided to the third- quarter of the health facilities.Conclusion: Total service readiness was very low in the diagnostic and medicine facilities of Syangja. It demonstrates that there is a discrepancy between the present situation of the incremental trend of NCDs and the related level of service preparedness in primary health care settings. The development of the service readiness mechanism is imperative considering the increasing prevalence of non-communicable diseases in Syangja.Keywords: Non-communicable disease, Primary health facilities, Service Readiness